2014
DOI: 10.1371/journal.pone.0084773
|View full text |Cite
|
Sign up to set email alerts
|

Non-Syndromic Hearing Impairment in India: High Allelic Heterogeneity among Mutations in TMPRSS3, TMC1, USHIC, CDH23 and TMIE

Abstract: Mutations in the autosomal genes TMPRSS3, TMC1, USHIC, CDH23 and TMIE are known to cause hereditary hearing loss. To study the contribution of these genes to autosomal recessive, non-syndromic hearing loss (ARNSHL) in India, we examined 374 families with the disorder to identify potential mutations. We found four mutations in TMPRSS3, eight in TMC1, ten in USHIC, eight in CDH23 and three in TMIE. Of the 33 potentially pathogenic variants identified in these genes, 23 were new and the remaining have been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 41 publications
0
38
1
Order By: Relevance
“…Studies by Guipponi et al (2002) suggested the existence of autocatalytic processing, by which TMPRSS3 would become active, and the epithelial sodium channel (ENaC) could be a substrate of TMPRSS3 in the inner ear. Its contribution to hereditary deafness in the Indian population has recently been evaluated in a screening of 1739 individuals from 374 families with NSHL (Ganapathy et al, 2014). Analysis led to the identification of 3 TMPRSS3 novel mutations, including p.V116M, p.G243R, and p.C386R.…”
Section: Dfnb8/dfnb10/tmprss3mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies by Guipponi et al (2002) suggested the existence of autocatalytic processing, by which TMPRSS3 would become active, and the epithelial sodium channel (ENaC) could be a substrate of TMPRSS3 in the inner ear. Its contribution to hereditary deafness in the Indian population has recently been evaluated in a screening of 1739 individuals from 374 families with NSHL (Ganapathy et al, 2014). Analysis led to the identification of 3 TMPRSS3 novel mutations, including p.V116M, p.G243R, and p.C386R.…”
Section: Dfnb8/dfnb10/tmprss3mentioning
confidence: 99%
“…Data obtained from the tmc1 mutant mice suggest a possible role for TMC1 in mechanoelectrical transduction of sound by cochlear hair cells (Kawashima et al, 2015). In their screening of 374 families, Ganapathy et al (2014) identified eight TMC1 mutations. Among these, five were novel.…”
Section: Dfnb7/11/tmc1mentioning
confidence: 99%
See 1 more Smart Citation
“…Kalay reported TMC1 mutations in 6% (4/65) of the GJB2 ‐negative ARNSHL families and 4% (4/93) of all ARNSHL families from the northeast and east of Turkey (Kalay et al, 2005). TMC1 mutations account for 3.4% (19/557) of recessive deafness in Pakistani ARNSHL families, 3.5% (3/85) in Tunisian families (Tlili et al, 2008), and 1.6% in India (Ganapathy et al, 2014). The novel mutations are all from families with consanguineous marriages.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of hearing impairments are attributable to genetic causes (Ganapathy et al, 2014), and 80% of hereditary hearing loss is non-syndromic (lacking other clinical symptoms). Up to Jan 2015, approximately 87 NSHL deafness genes have been identified (http://hereditaryhearingloss.org/main) and previously unknown genes that contribute to deafness are under investigation.…”
Section: Introductionmentioning
confidence: 99%